Pengaruh Pemanfaatan Teknologi Informasi Terhadap Peningkatan Kinerja Keuangan UMKM dengan Sistem Pengendalian Intern Sebagai Variabel Moderasi: Studi Penelitian pada UMKM Binaan BI Kota Gorontalo - Ebi Cahra Pulomoduyo; Usman Usman; Yustina Hiola (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the effect of information technology utilization on improving the financial performance of Micro, Small, and Medium Enterprises (MSMEs), with the internal control system serving as a moderating variable among Bank Indonesia-assisted MSMEs in Gorontalo City. This study employed a quantitative research method using primary data collected through questionnaires distributed to 46 Bank Indonesia-assisted MSMEs. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software to evaluate both the measurement model (outer model) and the structural model (inner model). The findings indicate that information technology utilization has a significant effect on improving the financial performance of MSMEs. The internal control system also has a significant effect on financial performance. Furthermore, the internal control system significantly moderates the relationship between information technology imply ton the success of sm dişital transaniat pen foreign odings imply that the success of MSMEs' digital transformation effective utilization of information technology but also on therimplementation of a sound internal control system to ensure that business manage dont is more effective, efficient, and sustainable.